PENERAPAN METODE DAKWAH PADA KAJIAN SUBUH DALAM MENINGKATKAN JAMAAH SUBUH DI MASJID AGUNG PASAMAN ISLAMIC CENTRE - Defrinal; M. Sahdani Harahap; Dahwir (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2024)
Programmed dawn study is a structured effort to encourage and increase the attendance of worshipers at dawn prayer time at the Great Mosque of Pasaman Islamic Centre. Through the delivery of interesting and meaningful studies, as well as the preparation of routine and systematic programmes, the preachers and mosque administrators hope to motivate the congregation to be more active and eager to attend the dawn study. This type of research is field research and qualitative method, descriptive approach, research that tries to describe and interpret objects or phenomena that are seen or that are developing in the field according to what is known through interviews and observations. The results of the study found one method used by the ustadz during the dawn study, namely the da'wah method al mauidzatil hasanah with elements of education, guidance, teaching, stories and speech containing advice for people who listen to it that satisfies the congregation.